Transactional Fish-for-Sex Relationships Amid Declining Fish Access in Kenya. (October 2015) - Fiorella, Kathryn J.; Camlin, Carol S.; Salmen, Charles R.; Omondi, Ruth; Hickey, Matthew D.; Omollo, Dan O.; Milner, Erin M.; Bukusi, Elizabeth A.; Fernald, Lia C.H.; Brashares, Justin S.
Highlights: Natural resources may be accessed through transactional fish-for-sex exchanges. On Lake Victoria's shores, fish declines affect initiation, duration and power dynamics in fish-for-sex relationships. Fish availability affects economic (e.g., price) and sexual (e.g., condoms) negotiations. A primary goal of fish-for-sex relationships is resources access, not just income. Summary: Women's access to natural resources for food and livelihoods is shaped by resource availability, income, and the gender dynamics that mediate access. In fisheries, where men often fish but women comprise 90% of traders, transactional sex is among the strategies women use to access resources. Using the case of Lake Victoria, we employed mixed methods (in-depth interviews, n = 30; cross-sectional survey, n = 303) to analyze the influence of fish declines on fish-for-sex relationships. We found that fish declines affect relationship duration and women's bargaining power. Our results have broad implications for the dynamics of economies dependent on increasingly scarce resources throughout the world.